CLIMATE CHANGE AND LABOR MOBILITY OF AGRICULTURAL HOUSEHOLDS: A REVIEW - Judijanto, Loso (Seven Editora, 2026)
Climate change has increasingly altered the livelihood conditions of agricultural households, particularly by influencing labor allocation and mobility decisions. Growing climate variability, extreme weather events, and production uncertainty have intensified scholarly attention on how rural households respond through labor mobility as part of broader adaptation processes. This review critically synthesizes recent empirical evidence on the relationship between climate change and labor mobility at the agricultural household level, focusing on emerging patterns, key drivers, and livelihood implications. This study employs a Systematic Literature Review (SLR) approach, following a transparent, structured screening process. Peer-reviewed journal articles were identified through the Scopus database using refined keyword combinations related to climate change, labor mobility, and agricultural households. From an initial pool of 5,191 records, successive filtering by relevance, publication year (2021–2025), language, and open-access status yielded 37 eligible articles for final analysis. Data were collected exclusively from secondary sources and analyzed using qualitative thematic synthesis and cross-study comparison. The findings reveal six dominant themes: climate variability and shocks as primary drivers of mobility, household economic vulnerability and income diversification strategies, spatial patterns of labor mobility, differentiated responses by gender and age, the role of institutional and policy mediators, and long-term implications for agricultural sustainability. The review shows that labor mobility functions both as an adaptive strategy and a potential source of new vulnerabilities, depending on household capacities and institutional contexts. In conclusion, climate-induced labor mobility represents a complex, context-dependent livelihood response rather than a uniform outcome of environmental stress. Future research is encouraged to integrate longitudinal data and policy-oriented analysis to capture dynamic household adaptation pathways better. DOI: https://doi.org/10.56238/sevened2026.008-067